PENGARUH DISPENSASI NIKAH TERHADAP TERBENTUKNYA POLA PIKIR MASYARAKAT DI KECAMATAN TUTUR KABUPATEN PASURUAN - Jazilatul Atoya Fauzia; Ibnu Jazari; Dwi Ari Kurniawati (Jurnal Hikmatina, 2021)
The number of requests for dispensation of marrige for underage marriages that have occurred has rasulted in many mindseats being formed, Which have resulted in decreased education due to underage marriages. From this phenomenon, the researcher wants to know the effect of marriage dispensation on the formation of the mindset of the community in Tutur District, Pasuruan Regency. The results of the study used a qualitative approach with the type of field reserch and data collection techniques used interviews, observation, and documentation. This is motivated by the fact that there are still many people who marry underage due to environmental factors, and also the concern of parents which then becomes the habit of the surrounding community. According to what happened in Tutur District, Pasuruan Regency.